Circularity in Aero-engine components production through additive manufacturing at GKN Aerospace Sweden - Senthilnathan, Sri Ram Gnanesh (My University, 2024)
The thesis explores the potential of additive manufacturing to promote the circular economy in aero-engine component manufacturing, focusing on GKN Aerospace Sweden´s resource optimization and waste reduction. The research identifies possible circular flows for the future material flow in the aero-engine components production through additive manufacturing. The study examines GKN Aerospace's various aeroengine production methods and identifies potential circular approaches, such as the reuse and recycling of metal powders, the implementation of closed-loop systems and recommendation of circular approaches to enhance sustainability. Furthermore, the thesis elucidates the role of additive manufacturing in ReSOLVE Framework to enable circular economy principles. The research also provides recommendations for a strategy plan to incorporate Additive Manufacturing technologies (AM) into a circular economy framework within the GKN Aerospace context.
Keywords: Circular Economy; Sustainability; Additive Manufacturing; R´s strategies; Circular Indicators; ReSOLVE framework; Aero-engine components; Aerospace